First Possession, History, and Young Children's Ownership Judgments. Issue 5 (8th March 2013) - Friedman, Ori; Van de Vondervoort, Julia W.; Defeyter, Margaret A.; Neary, Karen R.
Abstract : It is impossible to perceive who owns an object; this must be inferred. One way that children make such inferences is through a first possession bias—when two agents each use an object, children judge the object belongs to the one who used it first. Two experiments show that this bias does not result from children directly inferring ownership from first possession; the experiments instead support an alternative account according to which the first possession bias reflects children's historical reasoning. In Experiment 1, eighty‐five 3‐ to 5‐year‐olds only based inferences on first possession when it was informative about the past. In Experiment 2, thirty‐two 5‐year‐olds based ownership judgments on testimony about past contact, while disregarding testimony about future contact.